Jugglers by choice: ESL adult learners in distance education - Hussin, Habsah
ESL (English as a Second Language) adult learners in distance education are in-service teachers who undertake their Bachelor of Education on part-time basis, after being away from a formal learning context for some time, either to take care of the family or to pursue a career or both. The majority of them are female teachers who have clocked in more than ten years of teaching experience; and they have to do a tough balancing act of juggling between being homemakers, career persons and students again. This paper discusses the experiences, problems faced and the ways of resolving the problems; of two cohorts of such adult learners undertaking a program of distance education in ESL at a public university in Malaysia. Data were obtained from a set of questionnaires and qualitative interviews. The findings reveal the (physical, financial, emotional and spiritual) challenges faced by these adult learners in the course of their studies, their strategies of handling these challenges which in turn reveals their personality traits i.e. industrious, resilient, determined and organized. These jugglers by choice were successful in their studies due to their ability to multi-tasks which would augur well for their career and future undertakings.